East of Denver - Hill, Gregory, 1972- (New York : Dutton, 2012)
Arriving at his family's farm in Eastern Colorado to discover his father's home in a terrible state because of the dishonest machinations of a corrupt banker, Shakespeare Williams falls in with former classmates in a plot to rob the bank that has cheated them.
edited hb 2015-06-16
Keywords: Farm life -- Fiction; Fathers and sons -- Fiction; Colorado -- Fiction; Humorous fiction